Upper respiratory tract disease in cats: organisms involved, modulation of the immune response, and analysis of a novel treatment - Veir, Julia K., author; Lappin, Michael R., advisor; Dow, Steven W., committee member; Maggs, David J., committee member; Twedt, David C., committee member (Colorado State University. Libraries, 2007)
This work evaluated organisms detected by microbiologic culture and molecular biology techniques in acute upper respiratory disease in shelter cats. Compared to other studies, similar detection rates were found for feline herpesvirus-1 (FHV-1) and Bordetella bronchiseptica but in our study population, there was a low incidence of Chlamydophila felis and calicivirus. Our results suggest that results from samples collected from the nasal or pharyngeal cavity were similar and detection by nucleic acid amplification techniques were suitable sampling strategies. A quantitative PCR assay was applied to nasal and pharyngeal samples and correlation between disease status and FHV-1 viral load was demonstrated, suggesting the assay may be useful clinically. A whole-blood proliferation assay was evaluated in order to assess the cellular immune response during an attempt to improve response to FHV-1 vaccination via supplementation with a strain of Enterococcus faecium (SF68) in kittens. The assay was shown to be reliable and used little blood, allowing for repeated testing in young animals. An increase in the percentage of CD4+ lymphocytes but not an increase in proliferative response to FHV-1 antigens secondary to supplementation was demonstrated. This may suggest an improvement in antigen processing abilities of the cats; however, more detailed studies are needed to prove this theory. In an attempt to ameliorate clinical signs in cats with rhinitis, response to a novel therapy of liposome DNA complexes was reported in three groups of cats: client-owned, shelter-owned, and healthy laboratory-animals. Detection of FHV-1 was low in the diseased animals, suggesting that FHV-1 is not involved in the disease or, alternatively, instigates a pathologic process and then is cleared. Also notable, no bias towards a Th2-type immune response leading to ineffective clearance of virus was detected in diseased cats. Administration of the liposome-complexes produced an innate immune response manifested by fever and malaise in placebo and treatment groups, which may have affected our ability to detect significant differences in the groups, as the placebo appeared to have an effect in cats as well. Reduction in severity of clinical signs was noted in client-owned treatment cats but not more acutely affected shelter-owned cats. Traditionally defined pathogens were not detected in several cats in our studies; further investigation of all organisms detected in these cats is warranted. Mycoplasma species were detected in the majority of these cats, therefore, a real-time PCR assay was developed to allow for quantitation of organismal load in future studies.